The risk of significant body weight gain and abdominal obesity during short-term treatment with olanzapine - Kostulski, Adrian; Pawełczyk, Tomasz; Rabe-Jabłońska, Jolanta (Archives of Medical Science, 2009)
Introduction: The prevalence of obesity has been increasing both in the United States and Europe. Epidemiological data have indicated an explicit increase in morbidity and mortality in a group of patients with BMI higher than 25. Important is also the problem of obesity in people with mental disorders (especially in psychotic patients) due to the introduction of atypical antipsychotics, e.g. olanzapine, after which significant body weight gains are often observed during short-term therapy. Material and methods: Sixty two patients who suffered from paranoid schizophrenia, aged from 18 to 45, were examined. Total change in body weight, height, waist and hip circumferences, BMI and WHR at both time points was evaluated. The type of obesity (considering the patients’ gender) and the correlation between initial BMI values and body weight gain during olanzapine treatment were also examined. Results: Higher gains have been observed in the group of patients who did not meet the obesity criteria at t = 0. A significant negative correlation between BMI (t = 0) and body weight gain during the 8-week olanzapine treatment was observed. A significant correlation between the patients’ gender and abdominal obesity was also observed at t = 1. Conclusions: Over 1/3 of examined patients exhibited a significant body weight gain during olanzapine treatment. Patients with normal weight or underweight before olanzapine treatment increased their body weight significantly more as compared to the patients with overweight or obesity found at t = 0. Abdominal obesity was diagnosed in the examined group at t = 1 more frequently in women than in men.